Safety Assessment of Lactiplantibacillus plantarum GUANKE Based on Whole-Genome Sequencing, Phenotypic, and Anti-Inflammatory Capacity Analysis - Simin Lu; Kun Yue; Siqin He; Yuanming Huang; Zhihong Ren; Jianguo Xu (Microorganisms)
Lactiplantibacillus plantarum GUANKE (L. plantarum GUANKE) is a Gram-positive bacterium isolated from the feces of healthy volunteers. Whole-genome sequencing analysis (WGS) revealed that the genome of L. plantarum GUANKE consists of one chromosome and two plasmids, with the chromosome harbors 2955 CDS, 66 tRNAs, and 5 rRNAs. The genome is devoid of virulence factors and Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) systems. It contains three intact prophage regions and bacteriocin biosynthesis genes (plantaricins K, F, and E), as well as seventeen genomic islands lacking antibiotic resistance or pathogenicity determinants. Functional prediction outcomes identified that the genome of L. plantarum GUANKE is closely related to transcription, carbohydrate transport and metabolism, and amino acid transport and metabolism. Carbohydrate-active enzymes (CAZymes) analysis and GutSMASH analysis revealed that the genome of L. plantarum GUANKE contained 100 carbohydrate-active enzyme genes and two specialized metabolic gene clusters. Safety assessments confirmed that L. plantarum GUANKE neither exhibited β-hemolytic activity nor harbored detectable transferable drug resistance genes. The strain exhibited remarkable acid tolerance and bile salt resistance. Cellular adhesion assays demonstrated moderate binding capacity to Caco-2 intestinal epithelium (4.3 ± 0.007)%. In vitro analyses using lipopolysaccharide (LPS)-stimulated macrophage models demonstrated that L. plantarum GUANKE significantly suppressed the secretion of pro-inflammatory cytokines (TNF-α, IL-6, IL-1β), exhibiting dose-dependent anti-inflammatory activity. In vivo experiments showed that L. plantarum GUANKE was involved in the regulation of the apical junction pathway and interferon pathway in colon tissue of normal mice.